RH5.1-CyRPA-Ripr antigen combination vaccine shows little improvement over RH5.1 in a preclinical setting - Healer, Julie; Thompson, Jennifer K.; Mackwell, Karen L.; Browne, Cecille D.; Seager, Benjamin A.; Ngo, Anna; Lowes, Kym N.; Silk, Sarah E.; Pulido, David; King, Lloyd D. W.; Christen, Jayne M.; Noe, Amy R.; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
RH5 is the leading vaccine candidate for the Plasmodium falciparum blood stage and has shown impact on parasite growth in the blood in a human clinical trial. RH5 binds to Ripr and CyRPA at the apical end of the invasive merozoite form, and this complex, designated RCR, is essential for entry into human erythrocytes. RH5 has advanced to human clinical trials, and the impact on parasite growth in the blood was encouraging but modest. The current study assessed the potential of a protein-in-adjuvant blood stage malaria vaccine based on a combination of RH5, Ripr and CyRPA. This identified the DPX® platform as the best performing formulation in potentiating P. falciparum inhibitory antibody responses to these proteins both individually and as combinations. The three antigens derived from RH5, Ripr and CyRPA protein formulated with DPX induced highly inhibitory parasite neutralising antibodies, respectively. Notably, RH5 either as a single antigen or in combination with Ripr and CyRPA, induced inhibitory antibodies that performed better than either CyRPA or Ripr and the three antigens together. These results indicate that an RCR combination vaccine may be difficult to formulate with respect to differential immunogenicity and leaves the development pathway open for other antigens to be combined with RH5 as a next generation malaria vaccine.